PENGARUH FEEDING, KECEPATAN POTONG PAHAT CARBIDE TERHADAP KUALITAS PEMBUBUTAN BAHAN BAJA S45C - Agist, Rizwan (Jurnal Teknik Mesin, 2014)
The lathe is a machine tool which plays an important role in the production process in the industry. In the process of turning the workpiece is gripped by rotating on its axis, while the cutting tool moves along the workpiece cut as a result there was an incision by a chisel to form grimly. In this process there are significant results due to surface roughness value of the incision. To get the ideal level of roughness is influenced by several parameters. In this study S45C steel workpiece as much as six pieces that will get different treatment in the course of the work, namely the variation of cutting speed of 145 m / min, 165 m / min and 185 m / min was used feeding 0.15 mm / rev and 0.2 mm / rev with the cutting depth of 0.5 mm to determine its effect on the quality of the surface roughness average lathe face. Then from 6 workpiece to the workpiece respectively determined 3 points for the surface roughness test using test equipment surfcorder SE 1700. The results of the surface roughness of steel best quality and the lowest of 1.95 lm obtained from turning the cutting speed of 165 m / minutes, the engine turns 1000 rpm, depth of cut of 0.5 mm and 0.15 mm feeding / rev. While most high surface roughness of 5.8 lm sebersar obtained from the lathe with a cutting speed of 185 m / min, the engine turns 1400 rpm, and the feeding of 0.2 mm / put.